Interdiffusion and atomic mobilities in bcc V–X (X = Mn, Sn and Ni) alloys: Measurement and modeling. (September 2021) - Wang, Fei; Du, Yong; Min, Qianhui; Du, Changfa; Wen, Shiyi; Liu, Huixin; Zhong, Liang; Zhang, Shuyan; Chu, Mingqiang; Liu, Yuling
Abstract: Totally 8 diffusion couples were prepared and the composition-dependent interdiffusion coefficients in bcc V–Mn, V–Sn and V–Ni alloys were measured between 1323 and 1503 K by means of Sauer-Freise method coupled with electronic probe microanalysis (EPMA) technique. The errors of the interdiffusion coefficients were computed by error propagation method. Based on the measured interdiffusivities and thermodynamic parameters from the literature, the atomic mobilities of bcc V–X (X = Mn, Sn and Ni) alloys were obtained by using the CALTPP (CALculation of ThermoPhysical Properties) program with the features of high efficiency and accuracy in the framework of CALPHAD (CALculation of PHAse Diagram) approach. For each system, the presently obtained atomic mobilities were validated by good agreement between the calculated interdiffusivities and the measured ones. The model-predicted concentration profiles in this work are consistent with the experimental ones. This work contributes to the establishment of the atomic mobility database containing V element and the key input for microstructure simulations in V-based alloys. Highlights: The interdiffusivities of V–X (X = Mn, Sn and Ni) alloys are measured. The atomic mobilities of metastable phases are obtained with semi-empirical methods and forward-simulation analysis. The first application for optimization of atomic mobilities by CALTPP in binary systems is performed.